Firms' and States' Responses to Laxer Environmental Standards - Cordella, Tito; Devarajan, Shantayanan (World Bank, Washington, DC, 2019)
On June 1, 2017, President Trump announced the United States' withdrawal from the Paris agreement on climate change. Despite this decision, American firms continued investing in low-carbon technologies and some states committed to tougher environmental standards. To understand this apparent paradox, this paper studies how a weakening of environmental standards affects the behavior of profit-maximizing firms. It finds that a relaxation of emission standards (i) may increase firms' incentives to adopt clean technologies, but not to pollute less; (ii) may negatively affect industry profitability if it is perceived as temporary; and, when this is the case, (iii) the unilateral adoption of stricter standards by large states may increase the expected profitability of every firm.